Isolasi dan Karakterisasi Rizobakteri Asal Tanah Salin dan Potensinya sebagai Pemacu Pertumbuhan Tanaman - Mrois, Jason; Bahrun, Andi; Nurhalima; La, Mudi (JURNAL AGRIMENT, 2023)
Research related to the isolation and characterization of rhizobacteria and their potential as plant growth promoters was carried out to support the development of environmentally friendly and sustainable agriculture. This research aims to isolate and characterize rhizobacteria from saline soil which have the potential to promote plant growth. This research was carried out for 2 months at the Agrotechnology Laboratory, Agronomy Unit, Faculty of Agriculture, Halu Oleo University, Kendari. The research was conducted using an experimental design. Research on testing rhizobacteria isolates as plant growth promoters was carried out using a completely randomized design with 3 replications. The research was carried out by isolating and characterization of rhizobacteria both morphologically (elevation, appearance, margins, color, shape, and size of microbes) and biochemically (nitrogen fixation test, phosphate solubilization, and IAA hormone synthesis) and continued with germination tests of local tomato seeds. Data from research on morphological, physiological, and biochemical tests of endophytic microbes were analyzed using descriptive analysis, while rhizobacteria tests on germination (maximum growth potential) were analyzed using analysis of variance. The results of the analysis showing a real effect were followed by the Duncan test at a confidence level of 95%. Based on the research results, 20 isolates were obtained. The isolates with the highest ability to fix nitrogen (isolates Ab01, Ab03, Ab05, and Bb07), phosphate solubilizers (Ab10 and Ab03), and the highest ability of bacteria to produce IAA were obtained from isolate Ab04 at 124.91 ppm and isolate Bb05 at 115.27 ppm. Meanwhile, the highest ability of rhizobacteria isolates to germinate seeds (maximum growth potential) was obtained in isolate Bb05 at 88.89% and isolate Ab04 at 82.22% when compared with other isolates and controls.